Recent advances in alkenyl sp² C-H and C-F bond functionalizations: scope, mechanism, and applications - Lu, Ming-Zhu (2023)
Alkenes and their derivatives are featured widely in a variety of natural products, pharmaceuticals, and advanced materials. Significant efforts have been made toward the development of new and practical methods to access this important class of compounds by selectively activating the alkenyl C(sp2)-H bonds in recent years. In this comprehensive review, we describe the state-of-the-art strategies for the direct functionalization of alkenyl sp2 C-H and C-F bonds until June 2022. Moreover, metal-free, photoredox, and electrochemical strategies are also covered. For clarity, this review has been divided into two parts; the first part focuses on currently available alkenyl sp2 C-H functionalization methods using different alkene derivatives as the starting materials, and the second part describes the alkenyl sp2 C-F bond functionalization using easily accessible gem-difluoroalkenes as the starting material. This review includes the scope, limitations, mechanistic studies, stereoselective control (using directing groups as well as metal-migration strategies), and their applications to complex molecule synthesis where appropriate. Overall, this comprehensive review aims to document the considerable advancements, current status, and emerging work by critically summarizing the contributions of researchers working in this fascinating area and is expected to stimulate novel, innovative, and broadly applicable strategies for alkenyl sp2 C-H and C-F bond functionalizations in the coming years.